Characteristics of wet‐spun and thermally treated poly acrylonitrile fibers. Issue 29 (15th April 2016) - Kirsten, Martin; Meinl, Juliane; Schönfeld, Katrin; Michaelis, Alexander; Cherif, Chokri
ABSTRACT: The performance of carbon fibers depends on the quality of the precursor and the conditions of the thermal treatment. In detail, for a PAN precursor fiber the viscosity of a spinning dope and the draw ratio during the spinning process needs to be considered. Through wet spinning, different types of PAN precursor fibers with defined spinning parameters, including solid content, solvent content in a bath, and especially draw ratio resulting in defined cross section diameters, were fabricated and analyzed with tensile tests, density investigations, SEM, TGA‐MS, FTIR, and XRD. The results show that the mechanical properties of the fibers correlate to crystallinity. The cross section diameter is strongly related to the morphology of the fibers after thermal treatment. By extending the postdrawing of PAN fibers high tenacities were obtained at the cost of the cross section shape. In addition, TGA measurements reveal trapped residues of the wet spinning process as well as show several chemical reactions takes place at the same time at different temperatures. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43698. Abstract :